Serous Retinal Detachment Associated with Dome-Shaped Macula and Staphyloma Edge in Myopic Patients before and after Treatment with Spironolactone - Álvaro Fernández-Vega Sanz; Carlos Mario Rangel; Eva Villota Deleu; Beatriz Fernández-Vega Sanz; Ronald Mauricio Sánchez-Ávila (Journal of Ophthalmology)
Objective. Serous retinal detachment (SRD) is a common anatomical complication associated with dome-shaped macula (DSM) and staphyloma margin in myopic patients. Here we described the anatomical and functional outcomes obtained with the use of oral spironolactone, a mineralocorticoid antagonist, in the management of myopic patients with SRD associated with DSM and staphyloma margin. Methods. We evaluated both eyes of twelve myopic patients with long-standing SRD associated with DSM or staphyloma margin. The patients were treated daily for six months with oral spironolactone 50 mg. Best-corrected visual acuity (BCVA) and central retinal thickness (CRT), determined by optical coherence tomography, were evaluated on the first day and on monthly follow-up visits. Results. Pretreatment BCVA (mean ± standard deviation) was 0.406 ± 0.324 LogMAR, and posttreatment BCVA was 0.421 ± 0.354 LogMAR (P=0.489). Pretreatment CRT was 323.9 ± 78.6 μm, and after six months of treatment it was significantly lower, 291.2 ± 74.5 μm (P=0.010). There were no treatment-related complications. Conclusions. We evaluated a novel treatment for SRD associated with DSM and staphyloma margin in myopic patients. After six months of treatment with the mineralocorticoid antagonist spironolactone, the subretinal fluid and CRT were significantly reduced; however, there was no improvement in BCVA.